OPTIMALISASI KEINGINTAHUAN DAN KEMANDIRIAN BELAJAR MELALUI SOCIAL INQUIRY BERBANTUAN KAHOOT DI SD NEGERI MANGKUBUMEN WETAN - Yance Cahyanda; Oktiana Handini; Dite Hastini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of implementing the social inquiry learning model supported by Kahoot media in optimizing curiosity and learning independence among fourth-grade students at SD Negeri Mangkubumen Wetan Surakarta in the 2024/2025 academic year. This research employed a descriptive qualitative approach with data collected through triangulation techniques, including observation, interviews, and documentation. The research subjects consisted of 28 students, the classroom teacher, and the principal. The findings indicate that integrating social inquiry with Kahoot significantly improved student’s curiosity, as shown by increased enthusiasm for asking question and exploring material-rising from an estimate of 30% to 50%. Meanwhile, learning independence began to develop through student’s initiative and responsibility, though not yet fully optimal. Kahoot fostered a learning environment that was interactive, fun, and competitive, thereby enhancing student motivation and engagement. In conclusion, the social inquiry model supported by interactive digital media such as Kahoot is effective in shaping students’ critical thinking, curiosity, and independence learning behavior